2003
DOI: 10.3171/foc.2003.15.1.8
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conscious sedation and general anesthesia for motor mapping and resection of tumors located near motor cortex

Abstract: Object The surgical treatment of tumors located near eloquent cortex carries a high risk of inducing worsening neurological deficits. Intraoperative electrocorticography techniques have been developed to help identify these areas at the time of surgery in an effort to minimize such risks. The optimal anesthetic technique for conducting these procedures, however, has never been determined. Methods The aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0
2

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 17 publications
2
13
0
2
Order By: Relevance
“…A higher rate of electrographic evidence of seizure in the GA group was also reported in another series. However, their mean stimulation amplitude in the awake group was higher than in the GA group 5 . In the present report, the percentage of existing preoperative seizures was similar between the two groups (GA group: 62.5%, awake group: 55%).…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…A higher rate of electrographic evidence of seizure in the GA group was also reported in another series. However, their mean stimulation amplitude in the awake group was higher than in the GA group 5 . In the present report, the percentage of existing preoperative seizures was similar between the two groups (GA group: 62.5%, awake group: 55%).…”
Section: Discussionsupporting
confidence: 51%
“…It is often determined by the practice and experience of the team. There have been conflicting results reported in the literature 5,6 . A recent report showed that the GA group had a better outcome in terms of postoperative neurological deficits and extent of resection 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given intraoperative cortical stimulation can identify eloquent areas, many authors routinely adopt this technique to guide brain lesion resections and to maintain integrity of the functional pathways 8 . vitaz et al 9 compared the use of local anesthesia with general anesthesia in patients submitted to resection of lesions adjacent to eloquent cortex and reported a higher success rate of stimulation in awake patients (100% versus 50%) who required a significantly lower stimulation current (5 mA versus 13 mA, p<0.0001). A recent randomized prospective study compared general anesthesia with awake surgery and found that better tumor cytoreduction and neurological improvement was seen in the former, demonstrating that this topic remains controversial 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Although a longitudinal electrode may improve the probability to cover the appropriate target on the motor strip, a perpendicular orientation offers a more selective stimulation and increases the number of bipolar electrical combinations that enable an analgesic effect (34)(35)(36)(37)(38). Conscious sedation as an anesthesia technique could improve the accuracy of iCM (10,58,65). Other technical alternatives may be developed, such as covering a larger zone of the functional cortex by two Resume electrodes (or a grid) or integrating transcranial magnetic coil stimulation in the navigation device (18).…”
Section: Icmmentioning
confidence: 99%